2020
DOI: 10.1038/s41418-020-00672-0
|View full text |Cite
|
Sign up to set email alerts
|

Identification and functional characterization of new missense SNPs in the coding region of the TP53 gene

Abstract: Infrequent and rare genetic variants in the human population vastly outnumber common ones. Although they may contribute significantly to the genetic basis of a disease, these seldom-encountered variants may also be miss-identified as pathogenic if no correct references are available. Somatic and germline TP53 variants are associated with multiple neoplastic diseases, and thus have come to serve as a paradigm for genetic analyses in this setting. We searched 14 independent, globally distributed datasets and rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 76 publications
1
40
0
Order By: Relevance
“…Our results show that the p53 content in SDS-OBs was significantly higher (p < 0.05) compared to that in H-OBs (Figure 5b). This increase could not be ascribed to activating mutations of the Tp53 gene, as the sequencing of the coding region of Tp53 performed on RNA from SDS-OBs (n = 11) and H-OBs (n = 4) only showed the presence of the missense SNP rs1042522 in all the subjects, which occurs in the worldwide population [33]. To find the possible link between p53 and collagen and ALP, we treated SDS-OBs with a small interference RNA (siRNA, 5nM) targeting Tp53.…”
Section: High P53 Levels Are Involved In Sds-ob Functional Impairmentmentioning
confidence: 92%
“…Our results show that the p53 content in SDS-OBs was significantly higher (p < 0.05) compared to that in H-OBs (Figure 5b). This increase could not be ascribed to activating mutations of the Tp53 gene, as the sequencing of the coding region of Tp53 performed on RNA from SDS-OBs (n = 11) and H-OBs (n = 4) only showed the presence of the missense SNP rs1042522 in all the subjects, which occurs in the worldwide population [33]. To find the possible link between p53 and collagen and ALP, we treated SDS-OBs with a small interference RNA (siRNA, 5nM) targeting Tp53.…”
Section: High P53 Levels Are Involved In Sds-ob Functional Impairmentmentioning
confidence: 92%
“…Over ten assays for the determination of p53 activity at different levels have been used to evaluate compounds that can rescue p53 mutants. These include the differential scanning fluorimetry (DSF) assay ( Zhang et al., 2018 ), PAb1620 immunoprecipitation (IP) assay ( Xirodimas and Lane, 1999 ), luciferase reporter assay ( Doffe et al., 2020 ), PAb1620 ELISA assay, PAb1620 immunostaining assay, electrophoretic mobility-shift assay, biotin-DNA pull-down assay for assessing DNA-binding ability, various p53 target expression assays, etc. Some assays such as PAb1620 immunostaining assay are not highly sensitive in our hands, presumably due to the challenge in maintaining structural PAb1620 epitope during paraformaldehyde fixation.…”
Section: Before You Beginmentioning
confidence: 99%
“…An earlier study found that Arg/Arg homozygotes induce apoptosis more efficiently as compared to Pro/Pro homozygotes through the arrest of cell cycle in G1 phase (Pim and Banks, 2004), however, this observation is not supported by a recent study where wild-type p53 was indistinguishable from the variant forms in its apoptotic function (Doffe et al, 2021).…”
Section: Proline Rich Domain [Identified Polymorphism: Rs1042522 G>c (Pr72p)]mentioning
confidence: 86%
“…It presents in the PRD of p53. This domain regulates apoptosis and growth suppression of cell (Doffe et al, 2021;Almutairi et al, 2021). The SNP results in the missense substitution of proline (Pro) by arginine (Arg) (dbSNP, 2021).…”
Section: Proline Rich Domain [Identified Polymorphism: Rs1042522 G>c (Pr72p)]mentioning
confidence: 99%
See 1 more Smart Citation